THE ADDITION OF BOVINE SERUM ALBUMIN TO BELTSVILLE THAWING SOLUTION DILUENTS AGAINST MOTILITY AND VITALITY OF LANDRACE PIGS SPERMATOZOA - Suryanatha, I Made Agus; Bebas, Wayan; Laksmi, Desak Nyoman Dewi Indira (Buletin Veteriner Udayana, 2019)
This study aims to determine the effect of the addition of various bovine serum albumin ( BSA) concentrations on betsville thawing solution (BTS) ® extender to maintaining vitality and motility of spermatozoa on Landrace pigs. This study used Completely Randomized Design (CRD) with four treatments namely T0 (control): were given BTS® without BSA, T1: were given BTS® added BSA 5 mg/ml, T2: were given BTS® added BSA 10 mg/ml and T3: were given BTS® added BSA 20 mg/ml. Each treatment combination was repeated five times, with the total sample used was 20 samples. The measured variables in this study were the vitality and motility of Landrace pig semen. The results showed that the addition of BSA to BTS® diluents could increase the vitality and motility of spermatozoa on Landrace pigs. Where the optimal concentration was 10 mg/ml in keeping stability and maintaining the osmosis pressure stable